Diagnostic value of leukocytosis in patients presenting to the emergency department with abdominal pain: A retrospective observational study - Erkan Boğa (Asian Journal of Medical Sciences, 2025)
Background: Abdominal pain is one of the most common complaints in emergency departments (EDs) and poses diagnostic challenges due to its broad differential diagnosis. Leukocytosis is frequently used as a biomarker in clinical evaluation; however, its diagnostic value in predicting surgical conditions remains unclear.